INTEGRATING NEURO-PEDAGOGICAL APPROACHES IN THE DEVELOPMENT OF INTERACTIVE E-TEXTBOOKS FOR FOSTERING CREATIVITY AND CRITICAL THINKING (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the integration of neuro-pedagogical approaches into the design and development of interactive e-textbooks with a focus on fostering creativity and critical thinking among future teachers. Neuro-pedagogy, as a scientific field combining neuroscience, psychology, and pedagogy, offers innovative insights into how the brain processes, stores, and applies knowledge. By embedding these principles into interactive e-textbooks, educators can create learner-centered environments that stimulate higher-order thinking, enhance motivation, and foster creative problem-solving. The study analyzes international practices, reviews experimental findings, and provides methodological recommendations for developing e-textbooks that support the cognitive and emotional needs of learners.